Using magnetic dynamics to measure the spin gap in a candidate Kitaev material - Xinyi Jiang; Qingzheng Qiu; Cheng Peng; Hoyoung Jang; Wenjie Chen; Xianghong Jin; Li Yue; Byungjune Lee; Sang-Youn Park; Minseok Kim; Hyeong-Do Kim; Xinqiang Cai; et al. (npj Quantum Materials)
Abstract Spin-orbit entangled materials have attracted widespread interest due to the novel magnetic phenomena arising from the interplay between spin-orbit coupling and electronic correlations. However, the intricate nature of spin interactions within Kiteav materials complicates the precise measurement of low-energy spin excitations. Using Na2Co2TeO6 as an example, we study these low-energy spin excitations using the time-resolved resonant elastic x-ray scattering (tr-REXS). Our observations unveil remarkably slow spin dynamics at the magnetic peak, whose recovery timescale is several nanoseconds. This timescale aligns with the extrapolated spin gap of ~1 μeV, obtained by density matrix renormalization group (DMRG) simulations in the thermodynamic limit. The consistency demonstrates the efficacy of tr-REXS in discerning low-energy spin gaps inaccessible to conventional spectroscopic techniques.